2013
DOI: 10.1083/jcb.201304095
|View full text |Cite
|
Sign up to set email alerts
|

Filamentous morphology of bacteria delays the timing of phagosome morphogenesis in macrophages

Abstract: Uptake of bacterial filaments by macrophages is characterized by a prolonged phagocytic cup stage and diminished microbicidal activity during phagosome maturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
95
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(103 citation statements)
references
References 70 publications
8
95
0
Order By: Relevance
“…It was recently reported that filamentous Legionella pneumophila cells are harder for professional phagocytes to engulf (91). These filaments are slowly phagocytized along the long axis of the cell, resulting in prolonged phagocytic cups that fail to develop complete hydrolytic activity, thus allowing escape of the pathogen from phagosomal killing in a filament length-dependent manner (91). Similar findings have also been reported for uropathogenic E. coli (UPEC), where bacillary cells are preferentially killed over their filamentous counterparts (85).…”
Section: Bigger Is Bettersupporting
confidence: 65%
See 1 more Smart Citation
“…It was recently reported that filamentous Legionella pneumophila cells are harder for professional phagocytes to engulf (91). These filaments are slowly phagocytized along the long axis of the cell, resulting in prolonged phagocytic cups that fail to develop complete hydrolytic activity, thus allowing escape of the pathogen from phagosomal killing in a filament length-dependent manner (91). Similar findings have also been reported for uropathogenic E. coli (UPEC), where bacillary cells are preferentially killed over their filamentous counterparts (85).…”
Section: Bigger Is Bettersupporting
confidence: 65%
“…One common theme that has emerged is the use of filamentation to evade phagocytosis-mediated killing by the host. It was recently reported that filamentous Legionella pneumophila cells are harder for professional phagocytes to engulf (91). These filaments are slowly phagocytized along the long axis of the cell, resulting in prolonged phagocytic cups that fail to develop complete hydrolytic activity, thus allowing escape of the pathogen from phagosomal killing in a filament length-dependent manner (91).…”
Section: Bigger Is Bettermentioning
confidence: 99%
“…These filaments display both increased size and aspect ratio, and consequentially their phagocytosis by neutrophils and macrophages is decreased (Horvath et al, 2011; Moller et al, 2012). Even when phagocytosis occurs, it is delayed, leading to disturbed phagosome maturation and decreased killing of ingested filaments (Prashar et al, 2013). One can easily imagine a similar process happening during the slow ingestion of large S. aureus clumps, potentially contributing to survival of staphylococci after phagocytosis.…”
Section: Role Of Clumping/agglutination In Diseasementioning
confidence: 99%
“…It has been observed that adhering Dr-positive E. coli forms filamentous forms at the cell surface of CHO-hDAF-␣5␤1 (189) or CHO-hDAF (234) cells. Filamentous bacteria residing within the phagosome escaped phagosomal killing as the bacteria manipulated the phagosome compartment by blocking the acquisition of hydrolytic components (235,236). Even though the intracellular vacuole-containing Dr-positive E. coli in HeLa cells lack the characteristics of a degradative compartment (189), no filamentous forms of Afa-or Dr-positive E. coli residing intracellularly have ever been observed.…”
Section: Other Factorsmentioning
confidence: 99%